The persuasive effect of advergames promoting unhealthy foods among children: A meta-analysis. (1st October 2018) - Folkvord, Frans; van 't Riet, Jonathan
Abstract: Multiple studies have examined the effects of advergames promoting unhealthy foods on eating behavior among children. Although the individual results of the existing studies suggest that advergames have a significant influence on (predictors of) eating behavior, a lack of clarity concerning the size of the effect may impede policy actions. Therefore, a meta-analysis was conducted to examine the strength of the effect of playing advergames that promote unhealthy foods on (predictors of) eating behavior among children. Five electronic databases were searched for relevant publications (Web of Science, PsychInfo, Pubmed, JSTOR, and SCOPUS). Fifteen articles were considered eligible for inclusion and analyzed in the meta-analysis. Employing a random-effects model to estimate the composite effect of advergames yielded a small-to-moderate and significant effect of g  = 0.30. Results showed that advergames promoting unhealthy foods induced unhealthy eating behavior among children. Although only a limited number of studies were included, this meta-analysis supports public health policy action that seeks to reduce children's exposure to unhealthy digital food marketing. Stricter regulation to protect children against new forms of (online) marketing techniques that promote unhealthy foods should be developed and implemented.